Tips from Former Smokers: A Content Analysis of Persuasive Message Features. (October 2016) - Skubisz, Christine; Miller, Alice; Hinsberg, Liis; Kaur, Simran; Miller, Gregory A.
Years of research on message design and effects provides insight regarding the most persuasive message appeals. The purpose of this study was to evaluate the content of the messages being presented in the Centers for Disease Control and Prevention's Tips from Former Smokers campaign. A content analysis of persuasive message design features was conducted to critically examine campaign content. Campaign materials were coded for the presence of message variables including emotional appeals, evidence presentation, message framing, attitude functions, and source characteristics. Four independent coders analyzed 122 campaign messages, including video, print, and social media posts. Results from this content analysis indicate that the campaign contained more fear and guilt appeals, than other emotions. Evidence was typically presented in the form of a narrative from sources with firsthand experience. Suggestions for persuasive message design in large-scale public health communication campaigns are discussed.